Pola Pendidikan Karakter Religius dalam Pembelajaran Daring SMP Plus Citra Madhinatul Ilmi (CMI) - Akhmad Syakir; Jamiatul Hamidah; Istiqamah Istiqamah (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
This study aims to determine the pattern of religious character education for students carried out at SMP Plus Citra Madhinatul Ilmi (CMI), especially in online learning. The research uses a qualitative approach through the case study method. Sources of research data were taken from interviews with informants consisting of principals, classroom teachers, Indonesian language teachers, English teachers, and Mathematics teachers. Research data were taken through in-depth interviews with all informants. The results showed that the cultivation of character education values ​​for SMP Plus Citra Madhinatul Ilmi (CMI) students can still be done in online learning. Character values ​​that are instilled in schools are religious values, nationalism, integrity, independence, and mutual cooperation. The pattern of religious character education in online learning is carried out using various easily accessible media and collaboration between parents and teachers in terms of supervision of students.